Very effective in teaching basic education faculty professors prepare d. Basic Education - Radhi, Ibtisam (Al-Adab Journal, 2019)
The study aimed at what comes up.1-. Identify the Very effective in effective teaching in College of education professors self.2-Identify the differences in the effectiveness of teaching on self as a variable type (male-female). current research society is determined by the basic education college professors and both sexes Mustansiriyah University and academic year (2018-2019) and sample (200) textbook and teaching staff researcher has built a headquarters Yas effectively teaching self and extract his results showed statistical characteristics:-. The basic education college professors have very effectively. There were differences between males and females in effective teaching self for male. Depending on the results, the researcher has developed a number of recommendations and proposals.